Simple analytic tool for spectral control of dipole plasmon resonance frequency for gold and silver nanoparticles - Derkachova, Anastasiya; Kolwas, Krystyna (Photonics Letters of Poland, 2013)
We give mathematically simple tool allowing predicting the dipole localized surface plasmon resonance frequency as a function of size for gold and silver nanoparticles in water. We compare the results with our previous general study resulting from strict solutions of the eigenvalue problem of metal nanospheres embedded in various dielectrics. Full Text: PDF References K. Kolwas , A. Derkachova a. and S. Demianiuk, "The smallest free-electron sphere sustaining multipolar surface plasmon oscillation", Comp. Mat. Sc. 35, 337 (2006). CrossRef A. Derkachova, K. Kolwas, "Size dependence of multipolar plasmon resonance frequencies and damping rates in simple metal spherical nanoparticles", Eur. J. Phys. ST, 144, 93 (2007). CrossRef K. Kolwas, A. Derkachova, M. Shopa, "Size characteristics of surface plasmons and their manifestation in scattering properties of metal particles", J.Q.S.R.T. 110, 1490 (2009). CrossRef K. Kolwas and A. Derkachova, "Plasmonic abilities of gold and silver spherical nanoantennas in terms of size dependent multipolar resonance frequencies and plasmon damping rates", Opto-Electr. Rev. 18(4), 429 (2010). CrossRef K. Kolwas and A. Derkachova, "Damping rates of surface plasmons for particles of size from nano- to micrometers; reduction of the nonradiative decay", J.Q.S.R.T., 114, 45 (2013). CrossRef C. Sönnichsen, T. Franzl, T. Wilk, G. Von Plessen and J. Feldmann "Plasmon resonances in large noble-metal clusters", 2002 New J. Phys. 4, 93 (2002). CrossRef H. Baida, P. Billaud, at all,. "Quantitative Determination of the Size Dependence of Surface Plasmon Resonance Damping in Single Ag@SiO2 Nanoparticles", Nano Lett. 9, 3463 (2009). CrossRef P.B. Johnson and R.W. Christy, "Optical Constants of the Noble Metals", Phys. Rev. B6, 4370?4379 (1972). CrossRef T. V. Teperik and V. V. Popov, "Radiative decay of plasmons in a metallic nanoshell", Phys. Rev. B 69, 155402 (2004). CrossRef F. Forstmann and R.R. Gerhardts, "Metal optics near the plasma frequency. ", J. Mod. Opt. 109, 291 (1982). CrossRef